Strategy, Tactics, and Home Advantage in Team Sports - Gonçalves, Bruno (2021)
One of the most intriguing effects of home advantage (HA) in team sports is how coaches, teams, and players prepare strategically and tactically depending on whether competing at home or away. This is reflected in the different approaches that coaches may use for home matches (e.g., more overall pressure, aggressive defence, quicker attacks, and more collective tactical behaviour during ball possession), thereby increasing the intensity and tactical assertiveness of players. Besides, coaches have evolved their decision-making, following knowledge based on pre-match research (e.g., studying the strengths and weaknesses of their opponents and how they depend on match venue) and in-match situations (e.g., substitutions or tactical changes), where information transfer is a critical issue for improving the chances of winning at home. This chapter will attempt to understand the concept of HA under the lens of strategy and tactics in team sports.